If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 3w = 6 Solving -6 + 3w = 6 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3w = 6 + 6 Combine like terms: -6 + 6 = 0 0 + 3w = 6 + 6 3w = 6 + 6 Combine like terms: 6 + 6 = 12 3w = 12 Divide each side by '3'. w = 4 Simplifying w = 4
| 4x+14=135 | | -20=-8+3x | | x+0.25x=425000 | | 5x-3=8x+24 | | 5e^2x+7=21 | | 9+4p-2=p+3pb+7 | | x-472/x^2 | | 4v+13=73 | | 3w-1=9 | | -3x^2y^2=0 | | 8x+16=2x+112 | | y^2+6v-59=0 | | 6x+6=-24+x | | 4x=-5y-8 | | 13-4x=x+4 | | x+26=121 | | (9x-5y)(9x-5y)= | | x+13=121 | | sin^2(x/2)-3sinx-4=0 | | 6c^2+15c^3= | | 7x-9=x+10 | | 10=4+2u | | X=20log(5.8) | | -18=3(-2+6)+2x | | 6(x)+5(19-x)=107 | | 2c+1=4c+-2 | | 30a^3b^4/50a^4b^2 | | 3h+2=10 | | t=18/36*14 | | t=18/36 | | 0+(-85)= | | t=18/36*148 |